Peningkatan kemampuan analisis konsep gaya dengan menggunakan model means ends analysis pada peserta didik kelas iv sekolah dasar - Anisyah Khalilatin; Sandra Bayu Kurniawan; Siti Wahyuningsih (Didaktika Dwija Indria, 2019)
The purpose of the research is to improve of analysis ability on force concept by applying Means Ends Analysis model. The subject were IV grade students of SD Negeri 4 Boyolali in academic year 2018/2019, totaling 40 students. This research was a classroom action research wich was held in two cycles. There were four stages in each cycle, which was planning, action, observation, and reflection. The data collection techniques were interviews, observations, tests, and documentation. Data analysis  echniques, interactive analysis models and comparative descriptive statistics. Data validity using source  riangulation and technical triangulation. Result research o show that averageclass on preaction score is 23,88 with 0% classical completeness. Then class average value increased in cycle I to 53 with 32,5% classical completeness, and in cycle II increased again to 78,35 with 80% classical completeness. Based on results research, can concluded that application of Means Ends Analysis model can improve of analysis abilityon force concept on the IV grade students of SD Negeri 4 Boyolali in academic year 2018/2019.Keyword: analysis ability, force concept, Means Ends Analysis    model, elementary school